Characteristics of Generation Z Piano Students From the Perspective of Piano Teachers - Ömür, Özlem (Australian International Academic Centre, 2021)
The aim of this research is to determine the characteristics of Generation Z piano students from the perspective of piano teachers. The sample of the study consists of 40 piano teachers working in state conservatories with piano departments in Turkey. The data were collected with the “Teacher Opinion Form” consisting of 24 questions, which took its final form with expert opinions, and the findings were tabulated. As a result of the research, it has been determined that the majority of Generation Z piano students are generally impatient, have high self-confidence but low self-awareness in terms of personality traits. In terms of studying and learning characteristics, they experience great difficulties in their individual studies without support, they do not know their own learning methods, they have difficulty in managing their study time properly, and their professional curiosity is not high. When students are evaluated according to their emotional state, they are temperamental, have difficulty accepting criticism and lose their belief in success quickly. Piano students, according to their digital literacy, are hasty and play fast due to the habit of quick action/quick response habit acquired from the digital environment, and they quickly get bored with the works they are practicing as they are unable to balance between the regular flow of new information in the digital environment and the flow in real life. It is also among the results obtained that the students of Generation Z, who were born into technology, do not use this technology efficiently in terms of contribution to the piano lesson. In the light of these results obtained, suggestions regarding the piano education of Generation Z and future field studies were presented.
Keywords: 4. Education